In true face : a woman's life in the CIA, unmasked - Mendez, Jonna; Wood, Wyndham (Public Affairs, 2024)
"Jonna Hiestand Mendez began her CIA career as a "contract wife," a second-class citizen who was hired as a convenience to her husband, a young officer stationed in Switzerland. She needed his permission to open a bank account or shut off the gas to her apartment, and she performed menial duties for the CIA. Despite battling sexism at all levels of the agency, Mendez's talent for espionage was clear, and she soon took on bigger and more significant roles. She lived under cover and served tours of duty all over the globe, as well as at CIA Headquarters. She confronted dangerous situations that called on her spy training: coming face to face with a rogue Jihadi who had brought down an American plane, and helping steal a top-secret encryption machine from a Soviet embassy, among other high stakes situations. She became an international spy and ultimately Chief of Disguise at CIA's Office of Technical Service--a kind of female American version of James Bond's famous "Q." In this breakthrough memoir, Mendez recounts not only the drama of her international spy career but the grit and good fortune it took for her to navigate the CIA's misogynistic world. She was undermined, harassed, and threatened, and saw colleagues experience worse. While maintaining a patriotic mission and working to advance her own career, she was a firsthand witness to the cost of this gendered culture, both to the women who worked there, and to the interests of the agency and the nation it serves. In True Face is both clear-eyed and dramatic: the story of an incredible spy career, and what it took to achieve it"--